A Cross-Cultural Analysis of English Writing Errors: Insights From Indian and Saudi Arabian Learners - Makdoomi, Sarwat Un Nisa (Journal of language teaching and research, 2025)
English is a widely used medium of communication globally. In countries like India and Saudi Arabia, English is incorporated into academic curricula to achieve higher global recognition and inclusivity. This study conducts a comparative analysis of undergraduate students from these two countries to gain better insights. The sample comprises 500 students, 250 from each country, who completed a structured questionnaire. The findings reveal that Indian students face greater challenges in writing error-free English compared to their Saudi counterparts. Mediation analysis indicates that social influence and intention significantly and partially mediate the occurrence of semantic and grammatical errors based on the students' national origins. Technical difficulties are identified as the most influential factor in causing these errors, both directly and indirectly, emphasizing the need to address this issue irrespective of the students' country. The comparative analyses undertaken in the study highlight the differences in the difficulties existing in English writing. Language plays a vital role in both countries, and the suggested measures along with the highlighted points from the students could effectively contribute to further improving its status. The study is holistic in nature, where the instances of difficulties are validated through statistical processes and have established a more effective method of analogy. Future research can extend this study by incorporating additional factors, such as the role of technology in generating a detailed investigation method about the influence of social factors. This approach can be further enriched with a qualitative investigation to add to the current body of knowledge.